Stereoselective construction of coconformational mechanically helical and topologically chiral [2]catenanes induced by point chirality - Haitong Tang; Yan Zou; Hai-Ning Zhang; Guo-Xin Jin (Proceedings of the National Academy of Sciences, 2025)
Supported by chiral stationary phase high-performance liquid chromatography HPLC (CSP-HPLC), examples of chiral mechanically interlocked organic molecules, including knots, rotaxanes, and catenanes, have been reported. However, the exploration of stereoselective construction of chiral cationic complexes, particularly those induced by point chirality, has been notably limited due to the constraints posed by the type of chiral chromatographic columns and separation efficiency. To address this, we have developed a construction strategy for generating coconformational mechanically helical and topologically chiral [2]catenanes through the induction of point chirality. In this study, by adjusting the symmetry of the ligand, we have easily realized the efficient construction of high-yield crystalline coconformational mechanically helical and topologically chiral [2]catenanes. Moreover, within the enantiomerically pure chiral environment of molecular self-assembly driven by L -alanine and L -valine residues in bidentate ligands, the coconformational mechanically helical and topologically chiral [2]catenanes exist exclusively as a single enantiomer, thus eliminating the need for laborious CSP-HPLC separation from racemic mixtures. The generation of the opposite enantiomer can be realized by employing unsymmetrical ligands containing corresponding D -alanine and D -valine residues, as confirmed through single-crystal X-ray diffraction, elemental analysis, electrospray-ionization time-of-flight mass spectrometry, solution-state NMR spectroscopy, and circular dichroism spectroscopy.